High durability recycled aggregate concrete and method of making same
Patent Information
- Application Number
- CN202611076726.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-09-01
AI Technical Summary
[0004]为了克服上述的技术问题,本发明的目的在于提供一种高耐久性再生骨料混凝土及其制备方法,解决了现有的再生骨料混凝土的耐久性不佳的问题
本发明的一种高耐久性再生骨料混凝土及其制备方法,通过将水泥、细骨料、再生骨料加入至搅拌机中混合均匀,之后加入掺杂微胶囊的环氧基硅橡胶、复合增强剂以及水混合均匀,之后加入减水剂混合均匀,之后浇筑成型并养护,得到高耐久性再生骨料混凝土;该制备方法利用再生骨料为骨料实现建筑废弃物资源化利用,然后向其中添加掺杂微胶囊的环氧基硅橡胶能够在混凝土中内部形成致密交联网络,还能利用其弹性缓冲能力提升混凝土的抗冻抗冲能力,抑制微裂纹的产生,向其中添加复合增强剂不仅能够起到桥接作用还能起到填充作用,进而抑制裂缝的产生与扩展,大幅度提升再生骨料混凝土的耐久性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of recycled aggregate concrete, and more specifically to a high-durability recycled aggregate concrete and its preparation method. Background Technology
[0002] With the acceleration of urbanization, the disposal of construction waste has become a major challenge. Recycled aggregate concrete is an effective way to alleviate the depletion of natural sand and gravel resources and reduce construction waste accumulation. However, recycled coarse aggregate has old mortar adhering to its surface, and its high porosity and crushing index result in abundant microcracks inside the recycled aggregate concrete. Moreover, the interface transition zone is thinner, which easily leads to a decrease in concrete strength, seriously affecting the durability and service performance of the concrete, thus limiting the further engineering application of recycled aggregate concrete.
[0003] Therefore, there is an urgent need for a composite technology that can synergistically improve the microstructure of recycled aggregates and strengthen the interface. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a high-durability recycled aggregate concrete and its preparation method, which solves the problem of poor durability of existing recycled aggregate concrete.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a high-durability recycled aggregate concrete, comprising the following components in parts by weight: 380-400 parts cement, 600-650 parts fine aggregate, 1300-1400 parts recycled aggregate, 7-9 parts water-reducing agent, 30-70 parts epoxy silicone rubber doped with microcapsules, 6-16 parts composite reinforcing agent, and 190-200 parts water. The epoxy-based silicone rubber of the doped microcapsules is prepared by the following steps: Step a1: Add octamethylcyclotetrasiloxane and tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 10-20 min at a temperature of 20-25℃ and a stirring rate of 300-400 r / min. Then raise the temperature to 75-85℃ and continue stirring and reacting for 1-2 h. Then raise the temperature to 110-120℃ and continue stirring and reacting for 4-5 h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step a2: Add octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 10-20 min at 20-25℃ and 300-400 r / min. Then raise the temperature to 80-85℃ and continue stirring for 1-2 h. Then raise the temperature to 110-115℃ and continue stirring for 10-20 min. Then add alkali gum and hexadecylheptasiloxane and continue stirring for 3-5 h. Then raise the temperature to 155-160℃ and continue stirring for 2-4 h. After the reaction is complete, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step a3: Add alkenyl silicone rubber and chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 20-25℃ and 300-400 r / min for 10-20 min. Then raise the temperature to 50-55℃ and continue stirring for 8-10 h. Add m-chloroperoxybenzoic acid and continue stirring for 30-40 h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 50-60℃ for 4-6 h to obtain epoxy silicone rubber. Step a4: Add diphenylmethane diisocyanate and isophorone diisocyanate to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir at 20-25°C and a stirring rate of 300-400 rpm for 40-60 minutes. Then add polyvinyl alcohol solution and stir at 3000-4000 rpm for 3-5 minutes. Finally, raise the temperature to 55°C. The reaction was carried out at -60℃ and stirred at a stirring rate of 300-400 r / min for 8-10 min. Then, 1,4-butanediol was added dropwise while stirring, with the dropping rate controlled at 1-3 drops / s. After the addition was completed, the reaction was stirred for 3-5 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged. The precipitate was washed 2-3 times with distilled water and then placed in a vacuum drying oven and dried at 40-50℃ for 1-2 h to obtain isocyanate microcapsules. Step a5: Add epoxy-based silicone rubber and xylene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser, and gas delivery tube. Purge with nitrogen for protection and stir for 30-40 minutes at a temperature of 20-25℃ and a stirring rate of 300-400 r / min. Then add isocyanate microcapsules and continue stirring for 20-30 minutes. After the reaction is complete, spread the reaction product in a mold and place it in a vacuum drying oven. Dry at a temperature of 90-100℃ for 2-4 hours. Then pulverize to a particle size of 0.5 mm to obtain epoxy-based silicone rubber doped with microcapsules.
[0006] In a preferred embodiment of the present invention, the ratio of octamethylcyclotetrasiloxane to tetramethylammonium hydroxide in step a1 is 10g:0.2g.
[0007] In a preferred embodiment of the present invention, the ratio of the amounts of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, alkali gum, and hexamethylheptasiloxane in step a2 is 85-90g: 15-25g: 0.015-0.025g: 0.06-0.08g.
[0008] In a preferred embodiment of the present invention, the ratio of alkenyl silicone rubber, chlorobenzene and m-chloroperoxybenzoic acid used in step a3 is 4-6g: 100-110mL: 0.03-0.11g.
[0009] In a preferred embodiment of the present invention, the ratio of diphenylmethane diisocyanate, isophorone diisocyanate, polyvinyl alcohol solution and 1,4-butanediol in step a4 is 1-2g: 10-12g: 50-60mL: 2-3g.
[0010] In a preferred embodiment of the present invention, the polyvinyl alcohol solution in step a4 is a PVA-1788 solution with a mass fraction of 0.5%.
[0011] In a preferred embodiment of the present invention, the ratio of epoxy-based silicone rubber, xylene, and isocyanate microcapsules in step a5 is 5g:70-80mL:0.3-0.9g.
[0012] In a preferred embodiment of the present invention, the composite reinforcing agent is prepared by the following steps: 3-Aminopropyltriethoxysilane, deionized water, and ethanol were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 2-3 hours at 20-25°C and a stirring rate of 300-400 r / min. Then, basalt short-cut fibers and calcium carbonate whiskers were added, and the mixture was heated to 70-80°C and stirred for another 10-15 hours. After the reaction was completed, the reaction product was cooled to room temperature, centrifuged, and the precipitate was washed 2-3 times with distilled water. The precipitate was then placed in a vacuum drying oven and dried at 60-70°C for 2-4 hours to obtain the composite reinforcing agent.
[0013] In a preferred embodiment of the present invention, the ratio of 3-aminopropyltriethoxysilane, deionized water, ethanol, basalt short-cut fibers and calcium carbonate whiskers is 0.8-2.6g:10-15mL:60-70mL:1-2g:4-5g.
[0014] In a preferred embodiment of the present invention, the average length of the basalt short-cut fibers is 18 mm; the average length of the calcium carbonate whiskers is 30 μm.
[0015] Secondly, this application provides a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step 1: Prepare the following by weight: 380-400 parts cement, 600-650 parts fine aggregate, 1300-1400 parts recycled aggregate, 7-9 parts water-reducing agent, 30-70 parts epoxy silicone rubber doped with microcapsules, 6-16 parts composite reinforcing agent, and 190-200 parts water. Step 2: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add microcapsule-doped epoxy silicone rubber, composite reinforcing agent, and water and mix evenly. Then add water-reducing agent and mix evenly. Finally, pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0016] In a preferred embodiment of the present invention, the cement is P·O 42.5 ordinary Portland cement.
[0017] In a preferred embodiment of the present invention, the fine aggregate is natural river sand with a fineness modulus of 2.6.
[0018] In a preferred embodiment of the present invention, the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25 mm, obtained by crushing waste concrete blocks, and has an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%.
[0019] In a preferred embodiment of the present invention, the water-reducing agent is PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd.
[0020] The beneficial effects of this invention are: This invention discloses a high-durability recycled aggregate concrete and its preparation method. The method involves mixing cement, fine aggregate, and recycled aggregate in a mixer until homogeneous. Then, epoxy-based silicone rubber doped with microcapsules, a composite reinforcing agent, and water are added and mixed until homogeneous. A water-reducing agent is then added and mixed until homogeneous. The mixture is then poured, molded, and cured to obtain high-durability recycled aggregate concrete. This preparation method utilizes recycled aggregate to achieve resource utilization of construction waste. The addition of epoxy-based silicone rubber doped with microcapsules forms a dense cross-linked network within the concrete, enhancing its elastic buffering capacity and improving its resistance to freezing and impact, while inhibiting the formation of microcracks. The addition of the composite reinforcing agent not only acts as a bridge but also as a filler, further inhibiting the generation and propagation of cracks and significantly improving the durability of the recycled aggregate concrete.
[0021] In the preparation of high-durability recycled aggregate concrete, an epoxy-based silicone rubber doped with microcapsules was first prepared. Octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, and hexadecylheptasiloxane were used as monomers to polymerize and form a silicone rubber containing a large number of alkenyl groups, yielding alkenyl silicone rubber. Then, using m-chloroperoxybenzoic acid as an epoxidizing agent, the alkenyl groups on the alkenyl silicone rubber were converted into epoxy groups, yielding epoxy-based silicone rubber. Finally, using diphenylmethane diisocyanate, isophorone diisocyanate, and 1,4-butanediol as raw materials, polyurethane-coated microcapsules of diphenylmethane diisocyanate and isophorone diisocyanate were formed. Isocyanate microcapsules were obtained by encapsulating isocyanate microcapsules, which were then mixed into epoxy-based silicone rubber to obtain microcapsule-doped epoxy-based silicone rubber. The elasticity and toughness of the epoxy-based silicone rubber doped with microcapsules can significantly improve the buffering performance of concrete. Furthermore, the epoxy groups in the epoxy-based silicone rubber can form chemical bonds with the concrete. After the isocyanate microcapsules are damaged and ruptured, the diphenylmethane diisocyanate and isophorone diisocyanate flow out and fill the resulting microcracks with chemical bonds, achieving repair and further expansion, thus greatly improving the freeze-thaw resistance of concrete.
[0022] In the process of preparing high-durability recycled aggregate concrete, a composite reinforcing agent was also prepared. Basalt short-cut fibers and calcium carbonate whiskers were modified using 3-aminopropyltriethoxysilane. The siloxane on the 3-aminopropyltriethoxysilane was hydrolyzed to form silanols, which were then grafted onto the surface of the basalt short-cut fibers and calcium carbonate whiskers. Amino groups were also introduced to obtain the composite reinforcing agent. After modification, the dispersion performance of the basalt short-cut fibers and calcium carbonate whiskers was significantly improved, allowing them to be uniformly dispersed within the concrete. The basalt short-cut fibers acted as a bridge, and the resulting three-dimensional network effectively transferred and dispersed stress. The calcium carbonate whiskers filled micropores and microcracks, inhibiting damage propagation. Furthermore, the amino groups reacted with the isocyanate groups in the isocyanate microcapsules, achieving efficient damage repair and significantly improving the durability of the concrete. Detailed Implementation
[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0024] Example 1: This embodiment describes a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Add 10g of octamethylcyclotetrasiloxane and 0.2g of tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 300r / min for 10min. Then raise the temperature to 75℃ and continue stirring for 1h. Then raise the temperature to 110℃ and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step S2: Add 85g of octamethylcyclotetrasiloxane and 15g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 10 min at 20℃ and 300 r / min. Then raise the temperature to 80℃ and continue stirring for 1 h. Then raise the temperature to 110℃ and continue stirring for 10 min. Then add 0.015g of alkali gum and 0.06g of hexadecylheptasiloxane and continue stirring for 3 h. Then raise the temperature to 155℃ and continue stirring for 2 h. After the reaction is completed, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step S3: Add 4g of alkenyl silicone rubber and 100mL of chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 300r / min for 10min. Then raise the temperature to 50℃ and continue stirring for 8h. Add 0.03g of m-chloroperoxybenzoic acid and continue stirring for 30h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 50℃ for 4h to obtain epoxy silicone rubber. Step S4: Add 1g of diphenylmethane diisocyanate and 10g of isophorone diisocyanate to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir at 20℃ and 300r / min for 40min. Then add 50mL of 0.5% PVA-1788 polyvinyl alcohol solution and stir at 3000r / min for 3min. Then raise the temperature to 55℃ and continue stirring at 300r / min for 8min. Then add 2g of 1,4-butanediol dropwise while stirring, controlling the dropping rate to 1 drop / s. After the addition is complete, continue stirring for 3h. After the reaction is complete, cool the reaction product to room temperature, then centrifuge. Wash the precipitate twice with distilled water and then place it in a vacuum drying oven and dry at 40℃ for 1h to obtain isocyanate microcapsules. Step S5: Add 5g of epoxy-based silicone rubber and 70mL of xylene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir for 30min at 20℃ and 300r / min. Then add 0.3g of isocyanate microcapsules and continue stirring for 20min. After the reaction is complete, spread the reaction product in a mold and place it in a vacuum drying oven. Dry at 90℃ for 2h and then pulverize to a particle size of 0.5mm to obtain epoxy-based silicone rubber doped with microcapsules. Step S6: Add 0.8g of 3-aminopropyltriethoxysilane, 10mL of deionized water and 60mL of ethanol to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen and stir for 2h at 20℃ and 300r / min. Then add 1g of basalt short-cut fibers with an average length of 18mm and 4g of calcium carbonate whiskers with an average length of 30μm. Continue stirring for 10h at 70℃. After the reaction is complete, cool the reaction product to room temperature, centrifuge, wash the precipitate twice with distilled water, and then place it in a vacuum drying oven and dry at 60℃ for 2h to obtain the composite reinforcing agent. Step S7: Prepare the following by weight: 380 parts cement, 600 parts fine aggregate, 1300 parts recycled aggregate, 7 parts water-reducing agent, 30 parts epoxy-based silicone rubber doped with microcapsules, 6 parts composite reinforcing agent, and 190 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S8: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add microcapsule-doped epoxy silicone rubber, composite reinforcing agent, and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0025] Example 2: This embodiment describes a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Add 10g of octamethylcyclotetrasiloxane and 0.2g of tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 350r / min for 15min. Then raise the temperature to 80℃ and continue stirring for 1.5h. After that, raise the temperature to 115℃ and continue stirring for 4.5h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step S2: Add 88g of octamethylcyclotetrasiloxane and 20g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 15min at 22℃ and 350r / min. Then raise the temperature to 82℃ and continue stirring for 1.5h. Then raise the temperature to 112℃ and continue stirring for 15min. Then add 0.020g of alkali gum and 0.07g of hexadecylheptasiloxane and continue stirring for 4h. Then raise the temperature to 158℃ and continue stirring for 3h. After the reaction is completed, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step S3: Add 5g of alkenyl silicone rubber and 105mL of chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 350r / min for 15min. Then raise the temperature to 52℃ and continue stirring for 9h. Add 0.07g of m-chloroperoxybenzoic acid and continue stirring for 35h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 55℃ for 5h to obtain epoxy silicone rubber. Step S4: Add 1.5g of diphenylmethane diisocyanate and 11g of isophorone diisocyanate to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 350 rpm for 50 min. Then add 55 mL of 0.5% PVA-1788 polyvinyl alcohol solution and stir at 3500 rpm. The reaction was carried out for 4 min, then the temperature was raised to 58℃ and the reaction was continued to be stirred for 9 min at a stirring rate of 350 r / min. Then, 2.5 g of 1,4-butanediol was added dropwise while stirring, with the dropping rate controlled at 2 drops / s. After the addition was completed, the reaction was continued to be stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, then centrifuged, and the precipitate was washed twice with distilled water. Then it was placed in a vacuum drying oven and dried at 45℃ for 1.5 h to obtain isocyanate microcapsules. Step S5: Add 5g of epoxy-based silicone rubber and 75mL of xylene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 22℃ and 350r / min for 35min. Then add 0.6g of isocyanate microcapsules and continue stirring for 25min. After the reaction is complete, spread the reaction product in a mold and place it in a vacuum drying oven. Dry at 95℃ for 3h and then pulverize to a particle size of 0.5mm to obtain epoxy-based silicone rubber doped with microcapsules. Step S6: 1.7 g of 3-aminopropyltriethoxysilane, 12 mL of deionized water, and 65 mL of ethanol were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred at 22 °C and 350 r / min for 2.5 h. Then, 1.5 g of basalt short-cut fibers with an average length of 18 mm and 4.5 g of calcium carbonate whiskers with an average length of 30 μm were added, and the mixture was heated to 75 °C and stirred for another 12 h. After the reaction was completed, the reaction product was cooled to room temperature, centrifuged, and the precipitate was washed twice with distilled water. Then, it was placed in a vacuum drying oven and dried at 65 °C for 3 h to obtain the composite reinforcing agent. Step S7: Prepare the following by weight: 390 parts cement, 625 parts fine aggregate, 1350 parts recycled aggregate, 8 parts water-reducing agent, 50 parts epoxy-based silicone rubber doped with microcapsules, 11 parts composite reinforcing agent, and 195 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S8: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add microcapsule-doped epoxy silicone rubber, composite reinforcing agent, and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0026] Example 3: This embodiment describes a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Add 10g of octamethylcyclotetrasiloxane and 0.2g of tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 85℃ and continue stirring for 2h. Then raise the temperature to 120℃ and continue stirring for 5h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step S2: Add 90g of octamethylcyclotetrasiloxane and 25g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25°C and 400r / min for 20min. Then raise the temperature to 85°C and continue stirring for 2h. Then raise the temperature to 115°C and continue stirring for 20min. Then add 0.025g of alkali gum and 0.08g of hexadecylheptasiloxane and continue stirring for 5h. Then raise the temperature to 160°C and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step S3: Add 6g of alkenyl silicone rubber and 110mL of chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 55℃ and continue stirring for 10h. Add 0.11g of m-chloroperoxybenzoic acid and continue stirring for 40h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 60℃ for 6h to obtain epoxy silicone rubber. Step S4: Add 2g of diphenylmethane diisocyanate and 12g of isophorone diisocyanate to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 60min. Then add 60mL of 0.5% PVA-1788 polyvinyl alcohol solution and stir at 4000r / min for 5min. Then raise the temperature to 60℃ and continue stirring at 400r / min for 10min. Then add 3g of 1,4-butanediol dropwise while stirring, controlling the dropping rate to 3 drops / s. After the addition is complete, continue stirring for 5h. After the reaction is complete, cool the reaction product to room temperature, centrifuge, wash the precipitate three times with distilled water, and then place it in a vacuum drying oven and dry at 50℃ for 2h to obtain isocyanate microcapsules. Step S5: Add 5g of epoxy-based silicone rubber and 80mL of xylene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 40min. Then add 0.9g of isocyanate microcapsules and continue stirring for 30min. After the reaction is complete, spread the reaction product in a mold and place it in a vacuum drying oven. Dry at 100℃ for 4h and then pulverize to a particle size of 0.5mm to obtain epoxy-based silicone rubber doped with microcapsules. Step S6: Add 2.6g of 3-aminopropyltriethoxysilane, 15mL of deionized water and 70mL of ethanol to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen and stir for 3h at 25℃ and 400r / min. Then add 2g of basalt short-cut fibers with an average length of 18mm and 5g of calcium carbonate whiskers with an average length of 30μm and continue stirring for 15h at 80℃. After the reaction is completed, cool the reaction product to room temperature, then centrifuge. Wash the precipitate three times with distilled water and then place it in a vacuum drying oven and dry at 70℃ for 4h to obtain the composite reinforcing agent. Step S7: Prepare the following by weight: 400 parts cement, 650 parts fine aggregate, 1400 parts recycled aggregate, 9 parts water-reducing agent, 70 parts epoxy-based silicone rubber doped with microcapsules, 16 parts composite reinforcing agent, and 200 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S8: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add microcapsule-doped epoxy silicone rubber, composite reinforcing agent, and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0027] Comparative Example 1: This comparative example illustrates a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Prepare the following by weight: 400 parts cement, 650 parts fine aggregate, 1400 parts recycled aggregate, 9 parts water-reducing agent, and 200 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and has an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S8: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0028] Comparative Example 2: This comparative example illustrates a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Add 10g of octamethylcyclotetrasiloxane and 0.2g of tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 85℃ and continue stirring for 2h. Then raise the temperature to 120℃ and continue stirring for 5h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step S2: Add 90g of octamethylcyclotetrasiloxane and 25g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25°C and 400r / min for 20min. Then raise the temperature to 85°C and continue stirring for 2h. Then raise the temperature to 115°C and continue stirring for 20min. Then add 0.025g of alkali gum and 0.08g of hexadecylheptasiloxane and continue stirring for 5h. Then raise the temperature to 160°C and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step S3: Add 6g of alkenyl silicone rubber and 110mL of chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 55℃ and continue stirring for 10h. Add 0.11g of m-chloroperoxybenzoic acid and continue stirring for 40h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 60℃ for 6h to obtain epoxy silicone rubber. Step S4: Add 2g of diphenylmethane diisocyanate and 12g of isophorone diisocyanate to a four-necked flask equipped with a stirrer, thermometer, reflux condenser, constant pressure dropping funnel, and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 60min. Then add 60mL of 0.5% PVA-1788 polyvinyl alcohol solution and stir at 4000r / min for 5min. Then raise the temperature to 60℃ and continue stirring at 400r / min for 10min. Then add 3g of 1,4-butanediol dropwise while stirring, controlling the dropping rate to 3 drops / s. After the addition is complete, continue stirring for 5h. After the reaction is complete, cool the reaction product to room temperature, centrifuge, wash the precipitate three times with distilled water, and then place it in a vacuum drying oven and dry at 50℃ for 2h to obtain isocyanate microcapsules. Step S5: Add 5g of epoxy-based silicone rubber and 80mL of xylene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 40min. Then add 0.9g of isocyanate microcapsules and continue stirring for 30min. After the reaction is complete, spread the reaction product in a mold and place it in a vacuum drying oven. Dry at 100℃ for 4h and then pulverize to a particle size of 0.5mm to obtain epoxy-based silicone rubber doped with microcapsules. Step S6: Prepare the following by weight: 400 parts cement, 650 parts fine aggregate, 1400 parts recycled aggregate, 9 parts water-reducing agent, 70 parts epoxy-based silicone rubber doped with microcapsules, and 200 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S7: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add epoxy silicone rubber doped with microcapsules and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour into molds and place in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0029] Comparative Example 3: This comparative example illustrates a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: 2.6 g of 3-aminopropyltriethoxysilane, 15 mL of deionized water and 70 mL of ethanol were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 3 h at 25 °C and 400 r / min. Then, 2 g of basalt short-cut fibers with an average length of 18 mm and 5 g of calcium carbonate whiskers with an average length of 30 μm were added, and the mixture was heated to 80 °C and stirred for another 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed three times with distilled water and then placed in a vacuum drying oven and dried at 70 °C for 4 h to obtain the composite reinforcing agent. Step S2: Prepare the following by weight: 400 parts cement, 650 parts fine aggregate, 1400 parts recycled aggregate, 9 parts water-reducing agent, 16 parts composite reinforcing agent, and 200 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3 The crushing value was 12.7%, and the old mortar adhesion rate was 17.1%; the water-reducing agent was PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd. Step S3: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add composite reinforcing agent and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0030] Comparative Example 4: This comparative example illustrates a method for preparing high-durability recycled aggregate concrete, comprising the following steps: Step S1: Add 10g of octamethylcyclotetrasiloxane and 0.2g of tetramethylammonium hydroxide to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 85℃ and continue stirring for 2h. Then raise the temperature to 120℃ and continue stirring for 5h. After the reaction is completed, cool the reaction product to room temperature to obtain alkaline gel. Step S2: Add 90g of octamethylcyclotetrasiloxane and 25g of tetramethyltetravinylcyclotetrasiloxane to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25°C and 400r / min for 20min. Then raise the temperature to 85°C and continue stirring for 2h. Then raise the temperature to 115°C and continue stirring for 20min. Then add 0.025g of alkali gum and 0.08g of hexadecylheptasiloxane and continue stirring for 5h. Then raise the temperature to 160°C and continue stirring for 4h. After the reaction is completed, cool the reaction product to room temperature to obtain alkenyl silicone rubber. Step S3: Add 6g of alkenyl silicone rubber and 110mL of chlorobenzene to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25℃ and 400r / min for 20min. Then raise the temperature to 55℃ and continue stirring for 10h. Add 0.11g of m-chloroperoxybenzoic acid and continue stirring for 40h. After the reaction is complete, cool the reaction product to room temperature and pour it into methanol. Then filter under vacuum and place the filter cake in a vacuum drying oven and dry at 60℃ for 6h to obtain epoxy silicone rubber. Step S4: Prepare the following by weight: 400 parts cement, 650 parts fine aggregate, 1400 parts recycled aggregate, 9 parts water-reducing agent, 70 parts epoxy-based silicone rubber, 16 parts calcium carbonate whiskers, and 200 parts water; the cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and an apparent density of 2560 kg / m³. 3 The crushing value is 12.7%, and the old mortar adhesion rate is 17.1%; the water-reducing agent is PC-1016 polycarboxylate high-performance water-reducing agent from Suzhou Xingbang Chemical Building Materials Co., Ltd.; the average length of the calcium carbonate whiskers is 30μm. Step S5: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add epoxy silicone rubber, calcium carbonate whiskers, and water and mix evenly. Then add water-reducing agent and mix evenly. Then pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
[0031] The high-durability recycled aggregate concrete of Examples 1-3 and Comparative Examples 1-4 were subjected to freeze-thaw cycle tests according to the rapid freezing method in GB / T 50082-2024 to test the mass loss rate.
[0032] The test results are shown in the table below: , Referring to the data in the table above, and based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the addition of epoxy-based silicone rubber doped with microcapsules and composite reinforcing agents can significantly improve the freeze-thaw resistance of recycled aggregate concrete, thus giving the recycled aggregate concrete of this application excellent durability.
[0033] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0034] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A high-durability recycled aggregate concrete, characterized in that, Includes the following components by weight: 380-400 parts cement, 600-650 parts fine aggregate, 1300-1400 parts recycled aggregate, 7-9 parts water-reducing agent, 30-70 parts epoxy silicone rubber doped with microcapsules, 6-16 parts composite reinforcing agent, and 190-200 parts water. The epoxy-based silicone rubber of the doped microcapsules is prepared by the following steps: Step a1: Octamethylcyclotetrasiloxane and tetramethylammonium hydroxide are stirred and reacted. After the reaction is completed, the reaction product is cooled to obtain alkaline gel. Step a2: Octamethylcyclotetrasiloxane and tetramethyltetravinylcyclotetrasiloxane are stirred and reacted, then alkali gum and hexadecyl heptasiloxane are added and the reaction is continued to be stirred. After the reaction is completed, the reaction product is cooled to obtain alkenyl silicone rubber. Step a3: The alkenyl silicone rubber and chlorobenzene are stirred and reacted, then m-chloroperoxybenzoic acid is added and the reaction is continued. After the reaction is completed, the reaction product is cooled and then poured into methanol. After vacuum filtration, the filter cake is dried to obtain epoxy silicone rubber. Step a4: Diphenylmethane diisocyanate and isophorone diisocyanate were stirred and reacted, then polyvinyl alcohol solution and 1,4-butanediol were added and the reaction was continued with stirring. After the reaction was completed, the reaction product was cooled, then centrifuged, and the precipitate was washed and dried to obtain isocyanate microcapsules. Step a5: Stir the epoxy-based silicone rubber and xylene to react, then add isocyanate microcapsules and continue stirring to react. After the reaction is complete, dry the reaction product and then pulverize it to obtain epoxy-based silicone rubber doped with microcapsules.
2. The high-durability recycled aggregate concrete according to claim 1, characterized in that, The ratio of octamethylcyclotetrasiloxane to tetramethylammonium hydroxide used in step a1 is 10g:0.2g.
3. The high-durability recycled aggregate concrete according to claim 1, characterized in that, The ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, alkaline gum, and hexamethylheptasiloxane in step a2 is 85-90g: 15-25g: 0.015-0.025g: 0.06-0.08g.
4. The high-durability recycled aggregate concrete according to claim 1, characterized in that, The ratio of alkenyl silicone rubber, chlorobenzene and m-chloroperoxybenzoic acid used in step a3 is 4-6g: 100-110mL: 0.03-0.11g.
5. The high-durability recycled aggregate concrete according to claim 1, characterized in that, In step a4, the ratio of diphenylmethane diisocyanate, isophorone diisocyanate, polyvinyl alcohol solution, and 1,4-butanediol is 1-2g: 10-12g: 50-60mL: 2-3g; the polyvinyl alcohol solution is a 0.5% PVA-1788 solution.
6. The high-durability recycled aggregate concrete according to claim 1, characterized in that, The ratio of epoxy-based silicone rubber, xylene, and isocyanate microcapsules in step a5 is 5g:70-80mL:0.3-0.9g.
7. The high-durability recycled aggregate concrete according to claim 1, characterized in that, The composite reinforcing agent is prepared by the following steps: 3-Aminopropyltriethoxysilane, deionized water, and ethanol were stirred and reacted. Then, basalt short-cut fibers and calcium carbonate whiskers were added and the reaction was continued with stirring. After the reaction was completed, the reaction product was cooled, centrifuged, and the precipitate was washed and dried to obtain the composite reinforcing agent.
8. The high-durability recycled aggregate concrete according to claim 7, characterized in that, The ratio of 3-aminopropyltriethoxysilane, deionized water, ethanol, basalt short-cut fibers, and calcium carbonate whiskers is 0.8-2.6g:10-15mL:60-70mL:1-2g:4-5g; the average length of the basalt short-cut fibers is 18mm; and the average length of the calcium carbonate whiskers is 30μm.
9. A method for preparing high-durability recycled aggregate concrete as described in any one of claims 1-8, characterized in that, Includes the following steps: Step 1: Prepare the following by weight: 380-400 parts cement, 600-650 parts fine aggregate, 1300-1400 parts recycled aggregate, 7-9 parts water-reducing agent, 30-70 parts epoxy silicone rubber doped with microcapsules, 6-16 parts composite reinforcing agent, and 190-200 parts water. Step 2: Add cement, fine aggregate, and recycled aggregate to a mixer and mix evenly. Then add microcapsule-doped epoxy silicone rubber, composite reinforcing agent, and water and mix evenly. Then add water-reducing agent and mix evenly. Finally, pour the mixture into a mold and place it in a curing room for 28 days to obtain high-durability recycled aggregate concrete.
10. A method for preparing high-durability recycled aggregate concrete according to claim 9, characterized in that, The cement is P·O 42.5 ordinary Portland cement; the fine aggregate is natural river sand with a fineness modulus of 2.6; the recycled aggregate is a continuously graded aggregate with a particle size range of 5-25mm, obtained by crushing waste concrete blocks, and has an apparent density of 2560 kg / m³. 3 The crushing value is 12.7%, and the old mortar adhesion rate is 17.1%; the water-reducing agent is PC-1016 polycarboxylate high-performance water-reducing agent.